The ball at Versailles : a novel - Steel, Danielle (Delacorte Press, 2023)
"A dazzling new novel from Danielle Steel, whose countless #1 New York Times bestselling novels have made her one of America's favorite storytellers"--
Keywords: Debutantes -- France -- 20th century -- Fiction; Balls (Parties) -- France -- 20th century -- Fiction; Versailles (France) -- 20th century -- Fiction; Paris (France) -- 20th century -- Fiction; Domestic fiction; Historical fiction; Romance fiction; Romance fiction; Novels